2001
DOI: 10.1089/089771501750291846
|View full text |Cite
|
Sign up to set email alerts
|

The Immunophilin Ligand FK506 Attenuates Axonal Injury in an Impact-Acceleration Model of Traumatic Brain Injury

Abstract: The immunophilin ligand, cyclosporin A (CsA), is effective in reducing the axonal damage associated with traumatic brain injury (TBI). Based upon extensive ultrastructural and immunohistochemical studies, the neuroprotection afforded by CsA appeared to be mediated via mitochondrial protection, specifically, the prevention of mitochondrial swelling and inhibition of mitochondrial permeability transition (MPT). However, the potential that CsA could also be neuroprotective via the immunophilin-mediated inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
77
2
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 34 publications
3
77
2
1
Order By: Relevance
“…19 Specifically, through using either the delayed administration of FK506 or induction of postrepetitive moderate hypothermia (32-33°C), we achieved remarkable axonal and vascular protection after the repetitive mTBI. 19 Consistent with previous observations from our lab, [20][21][22][23][24] we assume that use of the immunophilin ligand, FK506, as well as moderate hypothermia acted on multiple targets, including, but not limited to, calcineurin-mediated, oxygen radical-linked, and metabolically regulated cascades attenuating their genesis of both axonal and microvascular damage. 19 Although it remains to be determined, such protective effects suggest that these therapies may ultimately prove of use in those patient populations sustaining increased morbidity subsequent to secondary insults or those manifesting a second impact syndrome.…”
supporting
confidence: 87%
“…19 Specifically, through using either the delayed administration of FK506 or induction of postrepetitive moderate hypothermia (32-33°C), we achieved remarkable axonal and vascular protection after the repetitive mTBI. 19 Consistent with previous observations from our lab, [20][21][22][23][24] we assume that use of the immunophilin ligand, FK506, as well as moderate hypothermia acted on multiple targets, including, but not limited to, calcineurin-mediated, oxygen radical-linked, and metabolically regulated cascades attenuating their genesis of both axonal and microvascular damage. 19 Although it remains to be determined, such protective effects suggest that these therapies may ultimately prove of use in those patient populations sustaining increased morbidity subsequent to secondary insults or those manifesting a second impact syndrome.…”
supporting
confidence: 87%
“…Given that STEP is expressed in the hilus, but not in the GCL, these data indicate the effect of FK506 was the specific result of STEP inhibition. It should be noted that FK506 has been shown to have neuroprotective effects in a number of brain injury models (Butcher et al, 1997;Singleton et al, 2001). However, the mechanism by which FK506 provides protection has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Given the established utility of intra-axonal ␀-amyloid precursor protein (APP) pooling to identify axonal injury (Blumbergs et al, 1994;Sherriff et al, 1994a,b;Gentleman et al, 1995;Bramlett et al, 1997;Geddes et al, 1997;Okonkwo and Povlishock, 1999;Buki et al, 1999;Finnie et al, 2000;Stone et al, 2000;Singleton et al, 2001), antibodies targeting the C terminus of the APP protein were used as previously described to identify perisomatic axonal injury (Singleton et al, 2002) and to explore the relationship, if any, between those cells manifesting axotomy and those revealing somatic membrane perturbation. Because our previous study also identified the presence of terminal deoxynucleotidyl transferasemediated biotinylated UTP nick end-labeling-negative, necrotic neurons in close relation to other neurons sustaining in perisomatic axotomy, we also used the histochemical marker Fluoro-Jade (FJ), which selectively stains degenerating neurons independent of the mechanism of cell death (Schmued et al, 1997;Schmued and Hopkins, 2000).…”
Section: Methodsmentioning
confidence: 99%